Policy options for building resilience of crop production under climate change - Ministry of Agriculture, Livestock, Fisheries and Cooperatives, Kenya (2020)
Timely interventions and support to farmers are urgently required to mitigate these events. Given the national economic, food security, nutritional and health importance of crop production, there is an opportunity for national policies on agriculture and climate change to support a more robust and resilient future for Kenya’s food production.